تصور مقترح لتطبيق نظم شراكة الاتحادات الرياضية مع القطاع الخاص في مجال الاستثمار الرياضي - سلامة، عبدالمقصود معوض Salamah, Abdulmaqsoud Muawwad (جامعة أسيوط - كلية التربية الرياضية, 2022)
يهدف البحث الحالي إلى وضع تصور مقترح لتطبيق نظم شراكة الاتحادات الرياضية مع القطاع الخاص في مجال الاستثمار الرياضي، وذلك من خلال التعرف على طبيعة الشراكة بين الاتحادات الرياضية والقطاع الخاص في مجال الاستثمار الرياضي، إمكانات الاتحادات الرياضية تجاه الإستثمار مع القطاع الخاص، النظم والأساليب المتبعة لشراكة الاتحاد مع القطاع الخاص، آليات تحفيز المستثمرين وتقديم التسهيلات لهم للشراكة مع الاتحادات الرياضية، الوسائل الإعلامية المستخدمة لتفعيل عملية الشراكة مع القطاع الخاص، معوقات عملية الاستثمار في الاتحادات الرياضية. واستخدم الباحث المنهج الوصفى (أسلوب الدراسات المسحية)، يتمثل مجتمع البحث في العاملين بالاتحادات الرياضية المصرية بجمهورية مصر العربية ومجالس إدارات تلك الاتحادات، قام الباحث باختيار عينة البحث بالطريقة الطبقية العشوائية، وقد بلغت قوامها (١١٢) فردًا موزعة على الاتحادات بحيث تم تقسيم الاتحادات إلى اتحادات رياضات فردية وأخرى جماعية. ولجمع البيانات استخدم الباحث تحليل الوثائق والسجلات واستبيان واقع تطبيق نظم شراكة الاتحادات الرياضية مع القطاع الخاص في مجال الاستثمار الرياضي. وكانت من أهم النتائج التصور المقترح لتطبيق نظم شراكة الاتحادات الرياضية مع القطاع الخاص في مجال الاستثمار الرياضي يمكن أن يسهم الارتقاء بالموارد المالية للاتحاد وزيادة قدرته على الوفاء باحتياجاته وتحقيق أهدافه، وكانت من أهم التوصيات تطبيق التصور المقترح لشراكة الاتحادات الرياضية مع القطاع الخاص في مجال الاستثمار الرياضي. The current research aims to develop a proposed vision for the application of partnership systems of sports federations with the private sector in the field of sports investment by identifying the nature of the partnership between sport federations and the private sector in the field of sports investment, the potential of sport federations to invest with the private sector, Association with the private sector, mechanisms to stimulate investors and provide facilities for them to partner with sports federations, the media used to activate the process of partnership with the private sector, impediments to the process of investment in sports federations. The researcher used the descriptive method (survey method). The research society consisted of the employees of the Egyptian sports federations in the Arab Republic of Egypt and the governing bodies of these federations. Individual and collective sports federations.. To collect the data, the researcher used the analysis of documents and records questionnaire and questionnaire of the reality of the application of the systems of partnership sports unions with the private sector in the field of sports investment. One of the most important results was the proposed scenario for the application of the partnership systems of the sports federations with the private sector in the field of sports investment which could contribute to the improvement of the financial resources of the Union and increase its ability to meet its needs and achieve its objectives. The most important recommendations were the application of the proposed vision of the partnership of sport federations with the private sector in the field of sports investment.
Keywords: الاستثمار الرياضي -- الاتحاد الرياضي -- القطاع الخاص -- مصر